Self-management in professional orientation for young athletes - Gretsov A.G. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to reveal the scientifically approved psychological and pedagogical technology for young athletes to manage their professional expectations by themselves for the successful furthermore professional self-determination. Methods and structure of the research. The research was held on the base of the Institute of Physical Culture of the Herzen State Pedagogical University of Russia. Approximately, 202 students of the 1st and 2nd courses of the Institute, aged 17-20 years (educational programs «Physical Education», «Physical Culture and Health Technologies») had been envolved. Based on the analysis of literary and other information sources, as well as personal teaching experience, the main difficulties that are typical at the stage of the end of the career of an active athlete, when moving to other types of professional activity, were identified. A set of developments was created aimed at preparing young athletes to make a decision about their professional future and psychologically safe passage through the crisis of the end of the career of an active athlete. The developments were scientifically tested finally. Results and conclusions. Professional self-determination of young athletes is hampered by such factors as: insufficient motivation to resolve this issue and poor understanding of its relevance; low awareness of professions, criteria for their selection, the labor market; insufficient understanding of one's own inclinations and abilities; inability to devote sufficient resources to professional self-determination, since sports activities are a priority. It is advisable to prepare young athletes for further self-determination in the professional sphere not after the end of the period of active training and performances, but in advance, at the age of 16-20: at the same time when most of their peers who are not involved in sports solve similar problems. A technology for its implementation has been developed, including text and illustrative information and methodological materials, 6 psychodiagnostic questionnaires, a program of training sessions (24 hours), and career guidance training. The developments have been tested on a sample of students receiving physical education and sports education.